Mathematical models for determining the optimal rotation in forest plantations - Guera, Ouorou Ganni Mariel; Silva, José Antônio Aleixo da; Ferreira, Rinaldo Luiz Caraciolo; Álvarez Lazo, Daniel; Barrero Medel, Héctor (Instituto de Ecología, A.C., 2019)
In this paper, procedures are proposed for determining the technical, economic and technical-economic rotations in forest plantations. The classical criteria of maximum productivity were determined: annual average increase and maximum land expected value. For the determination of the rotations, in addition to using the analytical tools (by adjusting forest growth models) and graphical tools conventionally used, mathematical programming models were proposed: model R-01 based on integer linear programming for the determination of the mono-criteria rotations and the models R-02 and R-03 based on weighted integer goal programming and lexicographic integer goal programming, respectively, for multi-criteria rotation determination. The validity of the proposed models was verified through the consistency of the technical, economic and technical-economic rotation ages determined by diverse site index in Pinus caribaea Morelet var. caribaea Barr. & Golf. plantations. The technically optimal rotations varied between 31 years and 35 years according to the site index and the economically optimal rotations between 18 years and 21 years. It was noticed that the technical-economic rotations are highly influenced by the criterion of greater importance in both approaches. The results found for Pinus caribaea var. caribaea with these approaches indicated intermediate rotations between the technical and the economic ones, these varying between 23 years and 25 years.